Aligning with the agent of justice: schadenfreude following punishment of trust violators - Yam, PPC; Huang, F; Luo, X; Parkinson, B (Springer, 2023)
Four experiments used trust games to investigate schadenfreude’s effects on attitudes and behavior towards third parties who punish prior violations of participants’ trust. Across all studies, schadenfreude was stronger when trust violators received negative rather than positive outcomes, and participants’ perceptions that the violator deserved punishment positively predicted levels of schadenfreude. Further, participants had less favorable attitudes towards third parties who delivered more negative outcomes (Experiment 1), but attitudes and behavior were relatively more favorable when these negative outcomes were inflicted on trust violators (Experiment 2). Participants also had more favorable attitudes and behavior towards third parties who delivered punitive outcomes which did not themselves involve trust violations. Further, results were consistent with a statistical model where just world beliefs, deservingness, and schadenfreude serially mediated the effect of punishment on attitudes towards third-party punishers (Experiment 3). These results were replicated in the pre-registered Experiment 4 using a larger sample and more focused measures. Taken together, our findings are consistent with the view that schadenfreude following trust violations serves the social function of aligning relations with agents who administer retributive justice.